2018
DOI: 10.1177/0738894218788362
|View full text |Cite
|
Sign up to set email alerts
|

Civil conflict and voting behavior: Evidence from Colombia

Abstract: What are the effects of war on political behavior? Colombia is an interesting case in which conflict and elections coexist, and illegal armed groups intentionally affect electoral outcomes. Nonetheless, groups have used different strategies to alter these results. This paper argues that differential effects of violence on electoral outcomes are the result of deliberate strategies followed by illegal groups, which in turn result from military conditions that differ between them. Using panel data from Senate ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 39 publications
(35 reference statements)
3
20
0
3
Order By: Relevance
“…Similarly, but using a measure of armed group presence (rather than violence), Arjona (2016b) found that support for the agreement was 14 percent higher in communities with FARC presence than in communities with only paramilitary presence. Moreover, these results are also consistent with findings from other studies that have explored the differential effects of FARC versus paramilitary violence on Colombians' voting behavior more generally (Gallego 2018). 21 The analysis also shows that other factors had an impact on support for the peace agreement.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similarly, but using a measure of armed group presence (rather than violence), Arjona (2016b) found that support for the agreement was 14 percent higher in communities with FARC presence than in communities with only paramilitary presence. Moreover, these results are also consistent with findings from other studies that have explored the differential effects of FARC versus paramilitary violence on Colombians' voting behavior more generally (Gallego 2018). 21 The analysis also shows that other factors had an impact on support for the peace agreement.…”
Section: Resultssupporting
confidence: 88%
“…3 This study disaggregates exposure to violence by "who shot the bullets." To be sure, we are not the first to examine the effects of perpetrator identity on civilian attitudes (see, e.g., Gallego 2018;Lupu and Wallace 2019;Lyall 2010;Lyall et al 2013). However, to the best of our knowledge, this is the first study to do so in the specific context of attitudes toward peace.…”
Section: Exposure To Violence and Attitudes Toward Peacementioning
confidence: 96%
“…Election day was relatively calm, although illegal armed groups (comprised by guerrillas and paramilitaries) once more tried to interfere and alter the normal conduct of elections (Gallego (2011)).…”
Section: The 2011 Local Electionsmentioning
confidence: 99%
“…Es decir, los municipios con mayores tasas de violencia y donde hubo participación del partido FARC presentan, en promedio, menor NEP y mayor margen de victoria. Este hallazgo concuerda con estudios recientes que encuentran que el comportamiento y actitudes políticas en el país dependen de factores relacionados con el conflicto armado y la exposición a la violencia (Gallego, 2018;Tellez, 2018).…”
Section: Conclusiónunclassified